2019
DOI: 10.1155/2019/8549727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc on the Oxidative Stress Biomarkers in the Brain of Nickel-Treated Mice

Abstract: The overexposure to nickel due to the extensive use of it in modern technology remains a major public health concern. The mechanisms of pathological effects of this metal remain elusive. The present study was devoted to evaluate the effect of nickel on the oxidative state of the brain cells of mice and to assess whether zinc as redox state modulator could efficiently protect cells against nickel’s neurotoxicity. As oxidative stress biomarkers in the present study, we have measured the concentrations of reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In vivo models using injections of moderately high Ni doses resulted in increased expression/activity of various biomarkers. These biomarkers are associated with oxidative stress such as alkaline phosphatase, aspartate transaminase, oxidized lipids, malondialdehyde, or glutathione reduction (20,49,50). A study by Chen et al (18) generation of free radicals following NiCl2 administration showed that dichlorofluorescein fluorescence was not elevated until a concentration of 1 mM was used.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo models using injections of moderately high Ni doses resulted in increased expression/activity of various biomarkers. These biomarkers are associated with oxidative stress such as alkaline phosphatase, aspartate transaminase, oxidized lipids, malondialdehyde, or glutathione reduction (20,49,50). A study by Chen et al (18) generation of free radicals following NiCl2 administration showed that dichlorofluorescein fluorescence was not elevated until a concentration of 1 mM was used.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the reduction was not significant; all the treatment groups increased its level when compared to the OXL group. This effect could be attributed to the neuroprotective effect of each of zinc 56 and melatonin. 57 …”
Section: Discussionmentioning
confidence: 98%
“…increased its level when compared to the OXL group. This effect could be attributed to the neuroprotective effect of each of zinc 56 and melatonin. 57 Oxaliplatin increased the levels of the inflammatory markers and the treatment combination of zinc and melatonin demonstrated a better effect in this regard.…”
mentioning
confidence: 98%
“…The Comet assay which detects both the ssDNA and dsDNA breaks revealed significant changes, particularly after the Ag NP and CuO NP exposure. The effects of ZnO NP were minimal; this result might be linked with the possible protective role of Zn against oxidative stress [ 54 ]. In contrast, micronuclei formation, which corresponds to dsDNA breaks, was very limited in some significant data for the highest tested doses of NP.…”
Section: Discussionmentioning
confidence: 99%